Impact of COVID-19 on Relationship-Centred Residential Dining Practices. Issue 4 (2nd December 2021) - Keller, Heather H.; Trinca, Vanessa; Dakkak, Hana; Wu, Sarah A.; Bovee, Sabrina; Carrier, Natalie; Cammer, Allison; Lengyel, Christina; O'Rourke, Hannah M.; Rowe, Natalie; Slaughter, Susan E.; Quiring, Suzanne
Abstract: This study describes changes in dining practices and provider perspectives on meal-related challenges due to the coronavirus disease (COVID-19) pandemic. An online survey was disseminated between July and September 2020 through stakeholder networks and social media with 1, 036 respondents. Altered dining practices included residents eating in rooms (54.3%), spacing residents in common areas for meals (69.3%), and disposable dish use (44.9%). The most common mealtime challenges were reduced socializing opportunities at meals (29.3%), inadequate staffing (22.8%), reduced family/volunteer help (16.7%), and assisting residents to eat (10.5%). Many participants (72.2%) felt conflict balancing safety and relationship-centred care. Geographic region, home size, building age, respondent's job title, pre-pandemic relationship-centred practices, and mealtime satisfaction, and some pandemic-initiated practices were associated with mealtime challenges and feeling conflicted in binary logistic regression analyses. Considering trade-offs between safety and relational aspects of mealtimes during the pandemic is crucial.